Utilisation of Mangifera indica plant extracts and parts in antimicrobial formulations and as a pharmaceutical excipient: a review - Mojisola Atinuke Alaiya; Michael A. Odeniyi (SpringerOpen, 2023)
Abstract Background Antimicrobial resistance and the environmental threat posed by some synthetic antimicrobial agents necessitate more research into development of novel pharmaceutical products that are environmentally friendly. Also, the use of plant derived excipients is growing and opening up new avenue to solve current drug delivery issues in the pharmaceutical industry. Main body This review summarizes studies related to the antimicrobial property of Mangifera indica extracts, possible mechanisms of antimicrobial action and antimicrobial formulations from the plant and overview of researches relating to the use of M. indica as a pharmaceutical excipient. Electronic searches were conducted on databases such as Pub Med, Wiley Online Library (WOL) and Google Scholar with focus on published articles relating to M. indica. Inclusion and exclusion criteria include publications relating to antimicrobial properties of M. indica extracts, its antimicrobial formulations and its use as a pharmaceutical excipient. The electronic searches yielded about 190 articles. From the studies reviewed, the mechanisms of action of phytochemicals described corroborate the antimicrobial activity exhibited by M. indica extracts and its selected formulations. In addition, mango pectin was observed to possess potential as a pharmaceutical excipient. Very few previous review articles based their focus on incorporating mechanism of action of phytochemicals with antimicrobial activity. This review examined antimicrobial properties of M. indica extracts and formulations, major phytochemicals in the plant parts and their possible modes of action. In addition, the study assessed the use of natural polymer derived from mango plant as excipients in pharmaceutical and pharmacological preparations. Conclusion The study concluded that effective antimicrobial activity of mango plant extracts and formulations requires synergy of actions among various phytochemical constituents of the extract or formulation. It is recommended that more researches focused on discovery of new phytochemicals in M. indica, their mechanisms of action and effective utilization of the plant in the pharmaceutical industry should be further explored.